The function of Golgi apparatus in LRRK2-associated Parkinson’s disease - Wei, Yonghang; Awan, Maher un Nisa; Bai, Liping; Bai, Jie (Frontiers in Molecular Neuroscience, 2023)
Parkinson's disease (PD) is a chronic neurodegenerative disease associated with the intracellular organelles. Leucine-rich repeat kinase 2 (LRRK2) is a large multi-structural domain protein, and mutation in LRRK2 is associated with PD. LRRK2 regulates intracellular vesicle transport and function of organelles, including Golgi and lysosome. LRRK2 phosphorylates a group of Rab GTPases, including Rab29, Rab8 and Rab10. Rab29 acts in a common pathway with LRRK2. Rab29 has been shown to recruit LRRK2 to the Golgi complex (GC) to stimulate LRRK2 activity and alter the Golgi apparatus (GA). Interaction between LRRK2 and vacuolar protein sorting protein 52 (VPS52), a subunit of the Golgi-associated retrograde protein (GARP) complex, mediates the function of intracellular soma trans-Golgi network (TGN) transport. VPS52 also interacts with Rab29. Knockdown of VPS52 leads to the loss of LRRK2/Rab29 transported to the TGN. Rab29, LRRK2 and VPS52 work together to regulate functions of the GA, which is associated with PD. We highlight recent advances in the roles of LRRK2, Rabs, VPS52, and other molecules, such as Cyclin-dependent kinase 5 (CDK5) and protein kinase C (PKC) in the GA, and discuss their possible association with the pathological mechanisms of PD.